Microbiological profile of bile culture and its antimicrobial susceptibility pattern in endo-biliary stented patients undergoing cholecystectomy - Dewangan, Komal Prasad; Geddam, Srinivasa Rao; Nayak, Partha Sarathi (International Surgery Journal, 2022)
Background: The vast majority of common bile duct (CBD) stones was secondary, formed within the gall bladder (GB) and migrates down the cystic duct into CBD or rarely due to primary stones formed in CBD. Intra-operative bile culture prevents development of infectious complications and guide selection of future appropriate antibiotic prophylaxis. Hence, this study focussed on investigation of microbiological profile of routine bile cultures in endo-biliary stenting patients undergoing cholecystectomy. Methods: In this study, 50 patients with CBD stone(s) were undergone endoscopic retrograde cholangio-pancreatography (ERCP) followed by stenting and then cholecystectomy (either laparoscopically or open). GB extraction was done in a sterile bag and after opening sterile bag; bile was collected and sent for microbiological culture and sensitivity for analysis. Results: Most of the cases had cholelithiasis with choledocholithiasis (38.0%) which were significantly higher than other diagnosis (Z=2.51; p<0.05) and there was no significant association found between surgical site infections and bile culture positivity of studied patients (Z=9.61; p<0.0001). Among 35 patients with positive bile cultures, E. coli in 26 patients followed by Klebsiella species in 5 patients were the most prevalent bacteria isolates and over all, colistin (91.4%) and tigecycline (91.4%) were found as sensitive antibiotics. Also, certain strains of multi drug resistance E. coli in 6 patients were resistant to gentamicin/amikacin only sensitive to tigecycline and colistin, which was high. Conclusions: Most prevalent isolates microorganism is gram negative bacteria that were mostly gut bacteria and the incidence of post ERCP infection is high and drug resistance among the causative organism is common.